IL10 and IL12B polymorphisms each influence IL-12p70 secretion by dendritic cells in response to LPS - Peng, Judy C.; AbuBakar, Sazaly; Richardson, Michelle M.; Jonsson, Julie J.; Frazer, Ian H.; Nielsen, Lars K.; Morahan, Grant; Thomas, Ranjeny (Australasian Society for Immunology (ASI), 2006)
Dendritic cells (DC) are the main producers of the cytokine IL-12p70, through which they play a direct role in the development of IFN-gamma-secreting Th1 cells, costimulation of CTL differentiation and NK-cell activation. In contrast, IL-10, which is also produced by DC, negatively regulates IL-12 production. IL-12p70 production varies widely between individuals, and several polymorphisms in the gene encoding IL-12p40 (IL12B) have been identified that influence susceptibility and severity of infectious, autoimmune and neoplastic disease. Here we show that polymorphisms not only of IL12B, but also in the IL10 promoter, influence IL-12p70 secretion by monocyte-derived DC in response to LPS. Although IL12B promoter homozygotes were prone to making more IL-12p70, presence of the IL10 high genotype restricted IL-12p70 production in these individuals. These observations provide a further genetic control of IL-12p70 regulation and emphasize the complexity of production of this cytokine. They also suggest genotypes that might influence the outcome of DC immunotherapy.